Socialization of the personality, and the development of personal and professional potential during time in college - Moyseenko Karіna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article substantiates the relevance and prospects of studying socialization and the development of personal and professional potential. The article considers existing approaches and suggests the concept of assessment of the development of personal and professional potential (such as what?). The article also notes that one of the tasks of socialization and development of the potential in the individual is to ensure the formation of professionalism; starting before school and ending after graduation. The researcher obtained information about personal and professional focus, and career orientation of the personality. (obtained information from where?) The study is based on a sample in which pupils of the 11th class of students and graduates took part. The interrelation of personal and professional potential with the socialization and implementation of an individual in various spheres of life was demonstrated.